TRANSFORMASI SISTEM PENDIDIKAN NASIONAL MELALUI IMPLEMENTASI PEMBELAJARAN MENDALAM: SEBUAH ANALISIS PELUANG DAN TANTANGAN - Syarifuddin A.; Agus Tinus (CV. Lafadz Jaya, 2026)
Educational transformation in Indonesia is entering a crucial phase with the strengthening of the Deep Learning paradigm as a primary instrument to reconstruct the National Education System (Sisdiknas). This study aims to dissect the implementation dynamics of Deep Learning by mapping strategic opportunities and systemic challenges. Employing a qualitative method with a library research approach, this study critically synthesizes the latest regulatory documents, pedagogical literature, and policy implementation reports across regions. The findings indicate that Deep Learning offers transformative opportunities through the